Antibacterial Activity Test of Extract and Fraction of Jabon Stem Bark (Anthocephalus cadamba (Roxb) Miq.) Againts Staphylococcus aureus dan Escherichia coli - Bakri, Nur Fadilah; Pratiwi, Mustika Endah; Manemi, Putri Winduri; Gunawan, Elsye; Mende, Juniarto (Jurnal Mandala Pharmacon Indonesia, 2025)
The stem bark of the Jabon plant (Anthocephalus cadamba (Roxb) Miq.) is a plant used empirically as a traditional medicine in the Jayapura City area. This study aims to determine the antibacterial activity and effective concentration of Jabon stem bark extract and fraction (Anthocephalus cadamba (Roxb) Miq.) against the test bacteria. The method used in this study is the Kirby-Bauer disc diffusion method to measure the diameter of the inhibition zone of each treatment. The results showed that the extract and fraction had antibacterial activity. The effective concentration of the extract was demonstrated at a concentration of 500 ppm with a strong category against the test bacteria. In comparison, the fractions were shown at a concentration of 1000 ppm with a moderate category against the test bacteria. This study concludes that the extract and fraction of the stem bark of Jabon have antibacterial activity and have the potential to be further developed as an antibacterial agent.